Jostling Isaac: dynamic configurations of bodies and objects during a language problem solving event. Issue 1 (3rd April 2021) - David, Samuel S.; Cole, Mikel W.
ABSTRACT: This article, a case study of a single instance of collaborative translation in the classroom, explores the role of material mediation and embodied activity in the linguistic problem solving work of emergent multilinguals. We describe one teacher's lesson with a small group of Spanish speaking students in her 7th grade ESL classroom. Collaborative translation is an approach that leverages the translation process (defining, translating, reading, revising, and discussing) to engage students in close readings of the text as they draw on their metalinguistic knowledge to promote deeper comprehension. Using multimodal interaction analysis methods, this paper investigates what we refer to as language problem solving events (LPSEs), a connected series of interactions around a word or phrase whose translation is a subject of negotiation. Findings describe how the material arrangement of the activity gave all participants opportunity to watch and comment on the choices being made by the scribe, so the written translation came to mediate the activity not only as a product of collective effort but also as a co-participant in the evolving interaction. The orchestrated configuration of materials fostered collective activity, but the particular affordances of the material inscription simultaneously transformed linguistic choices into objects that re-mediated subsequent action.